Riverbank erosion in Hungary - with an outlook on environmental consequences - Szalai, Zoltán; Balogh, János; Jakab, Gergely (Hungarian Geographical Bulletin, 2013)
In the 19th century deforestation in the Carpathians and the growing population made flood control and river regulation an urgent task in the Carpathian Basin. As a result of shrinking active floodplains and cut-offs, the natural sedimentation/erosion equilibrium have been upset over the Hungarian Plain. The modified conditions have also changed the erosion patterns on minor floodplains. The present paper will outline the necessity for flood control, its effects and consequences for bank erosion. The present conditions and forms of bank erosion along the Hungarian rivers are considered and an overview is provided on the most important factors affecting bank protection with their socio-economic consequences in Hungary.